TANGGAP PERTUMBUHAN VEGETATIF BIBIT KAKAO (Theobroma cacao L.) DENGAN PEMBERIAN VERMIKOMPOS DAN AIR PADA BERBAGAI KAPASITAS LAPANG - Ichsan Destari Purba; Irsal Irsal; Jasmani Ginting (Universitas Sumatera Utara, 2014)
ABSTRACTResponse of cacao (Theobroma cacao L.) seedlings vegetative growth with the provision ofvermicompost and water at various field capacity. Research aim to know the response of cacaoseedlings vegetative growth with the provision of vermicompost and water at various field capacity.It was conducted at green house, Faculty of Agriculture USU’st about 25 m sea level on November2012 to February 2013 by using a randomized block design factorial with two factor that is the firstfactor were vermicompost (0%, 10%, 20% and 30% of media plant) and the second factor wereprovision of water at various field capacity (100%, 75%, 50% and 25%). The parameters observedwere seedling height, stem diameter, total of leaf area, seedling wet weight, seedling dry weight,root wet weight, root dry weight and water use efficiency. The result of research showed thatvermicompost significant to seedling height, stem diameter, total of leaf area, seedling wet weight,seedling dry weight, root wet weight, root dry weight and water use efficiency. And provision ofwater significant to seedling height, stem diameter, total of leaf area, seedling wet weight, root wetweight and water use efficiency. The interaction of vermicompost and water had not signifficantKey words : cacao, vermicompost, water